La formación del contrato electrónico en el marco de la Comunidad Andina (2012)
The influence of the Information and Communication Technology (ICT) in all the aspects of the society is an unquestionable fact that implies; for the Law; the inescapable responsibility of fostering the fulfillment of the declarations or objectives of the Society of Information. Today´s world; framed in a process of globalization and regional integration; heads to the normative harmonization. In line with the above; the present document studies the elements supporting the normative unification concerning the formation of the contract by electronic means in the Andean Community